TARI PASIHAN BHONDAN SAYUK SEBUAH MAKNA TEKS - Slamet MD (Gelar : Jurnal Seni Budaya, 2006)
Bondhan Sayuk compiled to be inspired by Enggar-Enggar dance which have preexisted. Sunarno as orderer dance conscious Bondhan Sayuk that this dance in the begining fill compiled karawitan song music by Marto Pa ngrawit, what motivat desire have baby. Studying Bondhan Sayuk can be understood if in the theatre of him between dancer which is one with other experience of different motion variation of. This matter happened caused by text meaning of different accompaniment music song text especially at middle Javanese song. This Research is more focused by about how audience and dancer mean song text in music dance related to dance motion expression. involved in Audience of complex situation that where they get " inspiration" momentary to determine the meaning. Dancer as perpetrator in text meaning of song text in his danced dance motion. Process giving mean text take place in complicated situation that, which realized or do not, re/ate to experience before audience see Dance Pasihan Bondhan Sayuk. Related to Text show dance Pasihan represent story or the dance story, usually such text here is]song which is there are in dance music. Show text dance Bondhan Sayuk, residing in in loaded musical context of meaning, hereinafter get form in show of dance will give framework think to dancer to express into dance form, and audience get meaning from show dance Bondhan Sayuk from song text and dance as a show which is global and go into effect at the time of show take place. In context this is text meaning become important because interaction from various above mentioned factor reach form finallyKeyword: Pasihan, Bondhan Sayuk, Meaning Text.